An Errors Analysis of Arabic Phoneme in Non-Arabic Speaking Students at Junior High School - Muslimin; M. Abdul Hamid; Uril Bahruddin; Mualimin Mochammad Sahid (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2021)
The Ability to pronounce correct phoneme is one of the basic elements in learning Arabic. This research aimed to obtain data about Arabic pronunciation errors in students at junior high school. The research approach is qualitative. The sample of this study was 30 students of the Al-Mahmud IT Junior High School in Bima, Indonesia which were selected by using a simple random sample technique. The data of this research were the results of the students' audiovisual recordings when reciting Arabic text. Data analysis used the analysis model of Tarigan's, namely; data collection, identification, description, explanation, classification and evaluation. The results of this study The causes of phoneme errors are: environment, interference and performance. Classification of errors consist of omission, adding mad and Substitution. Evaluation and suggestion; there some ways to develop in learning Arabic phoneme are: continuous practice, listening to Arabic audio and videos.